Third Trimester Placental Grading by Ultrasonography and its Relationship with Fetal Outcome - Begum, Farzana; Jesmin, Shahela; Khatun, Rokeya; Parvin, Somerose; Rahman, Anisur (TAJ: Journal of Teachers Association, 2020)
Background: Antenatal ultrasound assessment of placental morphology plays an important role in evaluating fetal health, revealing abnormalities, such as infract & calcification. Abnormal placental maturity is associated with poor pregnancy outcome. In some high risk pregnancy placental maturity is accelerated as in pregancy –induced hypertension (PIH), intrauterine growth retardation (IUGR), whether in other high risk cases like diabetes and Rh-isoimmunization there is delayed placental maturation. Objectives: This was a cross sectional type of descriptive study. The study was carried out to assess placental grading by USG in high risk and normal pregnancy for predicting neonatal outcome. Material and method: The study was carried out in the Department of Obstetrics & Gynaecology in collaboration with the Department of Radiology & Imaging of Rajshahi Medical College Hospital from January 2012 to December 2013. : A total 200 pregnant mother, attending the inpatient department constituted study population who delivered their babies at Rajshahi Medical College Hospital were selected in antenatal period for USG examination to detect placental grade. Result: Ultrasonography showed, 35% had Grade-II placental maturity, 33.5%- Grade-III, 25% Grade - I and 6.5% had Grade-0 maturity. Majority of the mother (75%) were normal and had healthy baby. The relationship of placental maturity with gestational age of mother in normal pregnancy and in high risk pregnancy was found to be statistically significant. Placental maturity and fetal outcome in normal pregnancy was found significantly associated (p<0.001) but in high risk pregnancy it was not associated significantly (p>0.5). Early maturation of placenta in hypertensive women and delayed maturation in diabetic women were observed. Conclusion: Sonographic diagnosis of grade-III placenta has been reported to be as excellent predictor of fetal lung maturity than difficult and hazardous invasive procedure like amniocentesis. TAJ 2020; 33(2): 94-99